Psychological Effects of COVID-19 on coaches` emotions. Competitive level differences - Evangelos, B.; Christos, K.; George, B. (Psychology and Behavioral Science International Journal, 2022)
To investigate any possible relation between Sport Professionals (coaches) and COVID-19. More specifically, to examine if quarantine, affected their emotional status. To succeed that, the Greek version of the ERQ questionnaire was used. The collected questionnaires were 605. The results revealed differences in both variables among the sample. "Elite" coaches were more positive psychologically oriented than their "Non-elite" colleagues. Study results proved that in Greece also, professional sports level was affected by the Pandemic.